2010
DOI: 10.1109/tps.2010.2052371
|View full text |Cite
|
Sign up to set email alerts
|

Impulsively Generated Wave Trains in a Solar Coronal Loop

Abstract: Impulsively generated fast magnetoacoustic wave trains in a solar coronal loop are numerically studied. The problem is considered as 2-D in space, and for the description, the full set of magnetohydrodynamic (MHD) equations is used. The numerical solution of the MHD equations is performed by means of the Lax-Wendroff algorithm on a uniformly structured mesh. The wavelet analysis of the obtained wave trains shows out the typical tadpole shapes, i.e., a narrow tail followed by a broadband head. In this paper, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…In particular, the numerical studies by Nakariakov et al (2004) and Shestov et al (2015) showed that the period and amplitude modulations in the wave trains transform into tadpole-shaped Morlet spectra. This spectral feature was actually seen in both radio (e.g., Jelinek & Karlicky 2010;Karlický et al 2013) and optical measurements (e.g., Katsiyannis et al 2003;Samanta et al 2016). …”
Section: Introductionmentioning
confidence: 68%
“…In particular, the numerical studies by Nakariakov et al (2004) and Shestov et al (2015) showed that the period and amplitude modulations in the wave trains transform into tadpole-shaped Morlet spectra. This spectral feature was actually seen in both radio (e.g., Jelinek & Karlicky 2010;Karlický et al 2013) and optical measurements (e.g., Katsiyannis et al 2003;Samanta et al 2016). …”
Section: Introductionmentioning
confidence: 68%
“…Using a two-dimensional (2D) MHD model with the Harris current sheet, they concluded that these wavelet tadpoles indicate the fast magnetoacoustic waves propagating in the reconnection plasma outflows. These studies were supported by numerical simulations made by Jelínek & Karlický (2010, where they compared the evolution of the fast magnetoacoustic waves in a dense slab and Harris current sheet depending on the plasma beta parameter and width of the waveguide. They found that an increase in the distance between the initial perturbation and the detection point increases the length of the tadpole tail.…”
Section: Introductionmentioning
confidence: 87%
“…In particular, the numerical studies by Nakariakov et al (2004) and Shestov et al (2015) showed that the period and amplitude modulations in the wave trains transform into Morlet spectra characterized by a narrow tail followed by a broad head. Given their shape, these spectra are called "crazy tadpoles", and were indeed found in both radio (e.g., Jelinek & Karlicky 2010;Karlický et al 2013) and optical measurements (e.g., Katsiyannis et al 2003;Samanta et al 2016). If the measured short-period signals can be interpreted this way, then their temporal and wavelet features can be exploited to yield such key information as the internal Alfvén speed, density contrast between loops and their surroundings, as well as the location of the impulsive source (e.g., Roberts et al 1984;Roberts 2008).…”
Section: Introductionmentioning
confidence: 98%